Hand palpation – patient’s saviour from advanced cancer - Ahmad Zawawi, Muhammad Zul Hazmi; Shalihin, Mohd Shaiful Ehsan (2020)
Background: Hand palpation is one of the essential steps involved in physical examination for patient presented with abdominal pain. It is essential and had been trained among medical students before eligible to practice as a medical doctor. Gastric tumor if large enough can be suspected from adequate abdominal examination in 10% of cases. It can presents as a simple non-specific abdominal pain or discomfort in 80% of cases in which can easily be missed if the doctor are not tentative enough with correct abdominal examination technique. Case Report: We would like to share a case of 59-year-old man, no known medical illness presented with dyspepsia for three weeks. Interestingly, he had no other associated symptoms like nausea, vomiting, abdominal distension, early satiety or alarming symptoms. He had sought medical attention to two previous clinics and was informed to have gastritis and given antiacids medications but not resolved. Results: As in other case, in line with WHO approach in primary care, we proceed further with clinical examination from peripheral to abdominal examination. Surprisingly, there is palpable mass at his epigastric area, ill-defined in margin, firm in consistency and non-tender. We refer this case urgently to surgical team with high possibility of gastric malignancy. CECT abdomen reveals huge mass at upper abdomen arising from posterior wall of stomach. He then was successfully managed with total gastrectomy and recovers well. Conclusion: This case highlights the important of clinical examination in all cases comes to our attention, regardless either benign in nature or short in presentation. This case might be miss if every medical professional assume dyspepsia as gastritis and come into conclusion without proper examination. This case proved that a good and simple abdominal examination in primary care setting indeed has save the life of this gentleman who might die if the possible diagnosis has not been made promptly.